10.2k views
3 votes
Factor. y^2 -11y+28

2 Answers

4 votes

Answer:

(y-5.5)(y+5.5)

Explanation:


User Ruchelle
by
6.4k points
3 votes

Answer:

(y - 7)(y - 4)

Explanation:

The given expression is y^2 - 11y + 28

Now find the factor of 28 such that when you add the factors, we have to get -11

The right factors of 28.

-7 * - 4 = 28

-7 + (-4) = -11

The right factors are -7 and -1

y^2 - 11y + 28 = y^2 -7y - 4y + 28

= y(y - 7) -4(y - 7)

= (y - 7)(y - 4)

Therefore, y^2 -11y + 28 = (y - 7)(y - 4)

Thank you.

User Kravietz
by
5.5k points